2020
DOI: 10.1177/1591019920976251
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the first pass effect and the platelet-lymphocyte ratio in acute ischemic stroke

Abstract: Purpose The aim of this study was to evaluate the relationship between platelet-lymphocyte ratio (PLR) and first pass effect (FPE) in patients with acute ischemic stroke (AIS). Our secondary goal was to investigate other laboratory, demographic or technical parameters that may be related to FPE and to search for independent predictors of FPE. Materials and methods Patients who underwent mechanical thrombectomy (MT) in our hospital between January 2017 and February 2020 were reviewed. Patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Lux et al did not provide groupwise data but reported that admission NLR was not significantly associated with SR. 55 One study also considered the first pass effect (FPE), where complete recanalization (mTICI 3) is achieved with a single pass and reported a lower NLR in the FPE group. 57…”
Section: Association Of Nlr With Srmentioning
confidence: 99%
“…Lux et al did not provide groupwise data but reported that admission NLR was not significantly associated with SR. 55 One study also considered the first pass effect (FPE), where complete recanalization (mTICI 3) is achieved with a single pass and reported a lower NLR in the FPE group. 57…”
Section: Association Of Nlr With Srmentioning
confidence: 99%
“…Hard fibrin-rich clots are associated to lower recanalization rates due to reduced clot integration within the SR and a decreased deformability that impairs inclusion into the aspiration catheter. 18,19 The ANA device, which has the capability to expand up to index artery diameter, showed high rates of recanalization even when hard fibrin-rich clots were used in an in vitro model. 9 In our study, the high rates of reperfusion were associated to remarkable rates of good (mRS score 0-2: 57.2%) and excellent (mRS score 0-1: 45.2%) functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Of these three studies, the differences between groups were significant only in Lee et al 33 ‘s work. Another study, reporting on the first pass effect (FPE), where complete recanalisation (mTICI 3) was achieved with a single pass, showed a significantly higher PLR in the non-FPE group, 35 further supporting an association of admission PLR with recanalisation outcomes.…”
Section: Resultsmentioning
confidence: 93%
“…Very few studies considered the association of dynamic PLR changes with outcomes, and thus, this could not be analysed. Finally, not all studies 12 , 13 , 17 , 22 , 34 , 35 excluded patients with active infection, malignancy, or chronic disease, which can influence lymphocyte count via systemic inflammation. 4 , 10 …”
Section: Discussionmentioning
confidence: 99%